Moving interfacial Griffith crack between bonded dissimilar media - S. Mukherjee; S. Das (Journal of Applied Mathematics)
The plane strain problem of determining strain energy release rate, crack energy, and crack-opening displacement (COD) for a moving Griffith crack at the interface of two dissimilar orthotropic half-planes is considered. The problem is reduced to a pair of singular integral equations of second kind which have finally been solved by using Jacobi polynomials. Graphical plots of the strain energy release rate, crack energy, and crack-opening displacement for the problem in different particular cases are presented.